2011
DOI: 10.1002/ange.201100708
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Responsive Polymeric Vesicles that Breathe

Abstract: Vesicles breathe CO2! A new type of vesicle that self‐assembles from amidine‐containing diblock copolymer displays “breathing” features. Treating the vesicles with CO2 or Ar can reversibly tune the expansion and contraction of the vesicular volume, as if a bubble is breathing (see picture, PAD=poly((N‐amidino)dodecyl acrylamide), PEO=poly(ethylene oxide), Rh=hydrodynamic radius).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 64 publications
1
83
1
Order By: Relevance
“…In this regard, some nascent effort has been made recently. Yuan and co-workers have shown that CO 2 can effectively adjust polymer vesicular sizes; [10] Zhaos group has showed that the micellization of block copolymers can be induced by CO 2 levels. [11] Beyond these discoveries, whether CO 2 is capable of stimulating polymeric shape transformation and modulating their self-assembly structures remains a momentous challenge.…”
Section: Qiang Yan and Yue Zhao*mentioning
confidence: 98%
“…In this regard, some nascent effort has been made recently. Yuan and co-workers have shown that CO 2 can effectively adjust polymer vesicular sizes; [10] Zhaos group has showed that the micellization of block copolymers can be induced by CO 2 levels. [11] Beyond these discoveries, whether CO 2 is capable of stimulating polymeric shape transformation and modulating their self-assembly structures remains a momentous challenge.…”
Section: Qiang Yan and Yue Zhao*mentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8] Amphiphilic block copolymers are known to self-assemble into a range of nanostructures such as micelles, cylinders, vesicles, large compound micelles, jellyfish, and worm-like structures. 14,[15][16][17][18][19][20][21][22] Unlike the synthesis of block copolymers, that of homopolymers needs only one step, and supramolecular assemblies with enhanced tenability can be achieved easily. 12 Zhang and Eisenberg summarized the effects of chemical structure, hydrophobic/hydrophilic ratio, concentration, temperature, and environment.…”
Section: Introductionmentioning
confidence: 99%
“…11). 104 These polymersomes with unique gas-responsivity were shown to have reversible distinctive expansion and contraction, therefore they can be regarded as functional "breathing" nanocontainers for periodically accelerating drug release. Based on this work, Zhao's group studied the CO 2 -driven self-assembly and shape transformation of PEO-b-PAD with a broad range of shapes.…”
Section: Gas-responsive Polymersomesmentioning
confidence: 99%
“…11 Schematic representation of the self-assembly of diblock copolymer PEO-b-PAD into vesicles and their reversible gas-responsive "breathing" in aqueous media as CO 2 -responsive polymersomes. 104 Except for CO 2 -responsive block copolymers, there have been also reports on CO 2 -responsive systems based on host-guest interactions. Zhao et al developed a CO 2 sensitive imidazole-containing supramolecular block glycopolypeptide.…”
Section: Gas-responsive Polymersomesmentioning
confidence: 99%